Do Character, Capacity, Capital, Collateral, and Conditions as Affect on Bad Loans - Ega Saputra; Siti Resmi; Hari Nurweni; Tri Utomo Prasetyo (DINASTI RESEARCH, 2020)
Research on the analysis of the use of 5 C (character, capacity, capital, collateral, and condition) in lending has been carried out. Analysis of lending is mostly seen from the perspective of lenders (banks or other lending institutions). In contrast to research in general, this study aims to analyze bad loan from the borrower perspective. This study examines and analyzes the effect of character, capacity, capital, collateral, and conditions (5C) on bad loans. This study uses primary data through questionnaires. The population is the borrower of funds in the Technical Service Unit at Local Government Finance Office, Sleman Regency, Yogyakarta Province, Indonesia. The sample was determined using purposive sampling and 105 respondents were obtained. Purposive sample criteria are fund borrowers who have difficulty in repaying loans and are included in the monitoring agenda. The results of the study prove that the character, capacity, and conditions affect on bad loans, while capital and collateral have no effect on bad loans